The importance of regular physical activity in sedentary subjects post-COVID-19 pandemic: literature review (Research, Society and Development, 2021)
The purpose of the present study was to review the effects of the COVID-19 pandemic on the level of physical activity and sedentary lifestyle. A search articles was carried out throughout Google Scholar database, including articles published until September 2021 and using as descriptors: 'Sedentary lifestyle', 'Physical activity and health', 'Health maintenance', and ‘COVID-19’. A total of 16.200 articles were found in the Google Scholar database and, after confirmed inclusion and exclusion criteria, a total of 13 articles were included. Mostly included articles indicate negative effects on the physical activity level and sedentary lifestyle throughout COVID-19 sanitary restrictions. Thus, it is possible to conclude that the population's health worsened and that it is directly related to the low level of physical activity and increased sedentary behavior. Thus, the authors reinforce the importance of maintaining regular physical activity.